Syntactic Pattern Recognition of Intermittent EEG Activity - Ferber, G. (Methods of Information in Medicine, 1985)
Up to now, computerised processing of EEG signals has entered the domain of clinical application at most with respect to background activity and. the recognition of some intermittent basic patterns.Although the EEG is a multichannel signal, this recognition is performed separately for each channel, taking into account at most the immediate past and future. The result is a set of intermittent basic patterns. They are to be looked at as constituents of “complex patterns” which correspond to the entities used in the visual assessment.In this paper we present a method of uniting these basic patterns by means of syntactic pattern recognition algorithms. Together with this process the basic patterns are validated or devalidated, and the resulting complex EEG pattern is allocated to one of several pattern classes. To demonstrate how this procedure works, an example of artifact recognition is used. In order to get an acceptable performance, the process of syntactic pattern recognition is divided into a sequence of three steps. The resulting algorithms can be used for assessing clinical routine EEG. Some results are reported.
Keywords: EEG Analysis; Syntactic Pattern Recognition; Multichannel Signal; Clinical Application